التسويق البنكي وأثره رضا الزبون - منداسي, ماجدة أمال (My University, 2019)
This study is based on one of the most important questions related to banking institutions which is the marketing of banking, the process of achieving objectives and developing the tasks of the process. The study aims to know the importance of marketing strategies in the Algerian banking institutions on the study. We used the descriptive analytical approach in the theoretical part, Banks and Strategies. The practical side of the study was based on the case of how to apply banking marketing in the study of Algeria and the sample of the local development bank - Mostaganem - the study, summarizing a range of results, including: • The local development bank in Musangan applied a strategic distinction to attract customers. • Local Development Bank to achieve its long-term goals.
بنك التنمية المحلية مستغانم
Keywords: التسويق البنكي ، رضا الزبون ، بنك التنمية المحلية